Electrocardiogram abnormalities in obese adolescents - Elizabeth Joan Salim; Eka Gunawijaya; Ni Putu Veny Kartika Yantie (Indonesian Pediatric Society, 2020)
Background Obesity in adolescents is a known risk factor for cardiovascular disease mortality and sudden cardiac death. Obesity is associated with a wide variety of electrocardiogram (ECG) abnormalities. Objective To assess prevalence and describe the ECG abnormalities in obese adolescents. Methods This cross-sectional study was conducted at Children’s Cardiology Clinic – Integrated Heart Center of Sanglah General Hospital, Denpasar, Bali, by recording ECGs of obese adolescents aged 11-15 years from several junior high schools from December 2016 to April 2017. The inclusion criteria were obese adolescents aged 11 to 15 years, who were willing to participate in the study and provided informed consent. Results A total of 78 ECGs of obese adolescents (60% male) were selected. Subjects’ mean weight and age were 82.6 (SD 15.2) kg and 13.2 (SD 1) years, respectively. Pre-hypertension was found in 25 (32%) subjects, while hypertension was found in 18 (23%) subjects. There were 29 (37%) subjects with abnormal ECGs. Sinus tachycardia was present in 13 (17%) subjects, and sinus arrhythmia was identified in 11 (14%) subjects. Eight (10%) patients experienced prolongation of QTc interval and 5 (6%) patients presented with prolongation of PR interval. There were no shifts of the P wave, QRS wave and T wave axes, changes of P wave morphology, low QRS voltage, T wave flattening, ventricular enlargement, or ST segment changes found in this study. Conclusion The prevalence of cardiac abnormalities based on ECG examination in obese adolescents is 37%, consisting of heart rhythm abnormalities, prolonged PR interval, and prolonged QTc interval.